Implementation of Character Education for Students in the Era of Digitalization - Selamat Karo-Karo; Marioga Pardede; Prietsaweny Riris T Simamora; Losten Tamba (Postgraduate, University of Mataram, 2023)
The aim of this research is to describe the importance of character education for students in the era of digitalization in producing students who are disciplined, honest, responsible, tolerant, self-confident, communicative and creative, in accordance with the ideals of Pancasila in order to develop moral students. The research method used was by distributing questionnaires, questionnaires, documentation. The questionnaire given regarding character was immediately filled in by all first semester students at the Indonesian Business and Computer Institute. The research results show that character education is very important to prevent moral and ethical decline, so character education must be promoted from the start of entering college. From the results of the research, students were provided with several main character values, including: religiousness, nationalism, integrity, independence and cooperation. Each value does not stand and develop independently, but interacts with each other, developing dynamically and forming a whole